Xanthohumol bulk-modified polyurethane for tracheal repair: A ′killing two birds with one stone' strategy for tailorable mechanics and durable anti-inflammatory efficacy - Siqiang Zheng; Li Xu; Qitao Bo; Erji Gao; Enkuo Zheng; Lei Xie; Bin Zhao; Jiaoyu Yi; Yang Li; Yong Xu; Yao Wang; Bo Tao (Materials Today Bio)
Restoring tracheal defects remains a significant challenge in tissue engineering and regenerative medicine. Current scaffolds fall short of achieving optimal tracheal repair due to unmatched mechanical properties and limited anti‐inflammatory properties. In this study, we incorporated the natural plant‐derived anti-inflammatory molecule Xanthohumol (XN) into the backbone of a degradable polyurethane (PEUU) to create a porous PEXUU scaffold with tailorable mechanical properties and sustained anti‐inflammatory activity. Materials Studio software was initially employed to simulate the feasibility of synthesizing the PEXUU elastomer using XN as a chain extender and poly(ε‐caprolactone) as the soft segment. Mechanical tests confirmed the synthesized PEXUU elastomer exhibited excellent elasticity and fatigue resistance that closely mimic the mechanical properties of the natural trachea. The PEXUU elastomers were then processed into porous scaffolds via thermally induced phase separation, exhibited high porosity and favorable hydrophilicity while providing durable XN release kinetic in a sustained manner during degradation. In vitro co‐culture studies demonstrated that the scaffold not only exhibited favorable biocompatibility and supported cartilage regeneration but also effectively downregulated pro‐inflammatory factor expression and promoted the polarization of M1 macrophages toward the M2 phenotype. Furthermore, in vivo experiments revealed that implantation of the PEXUU scaffold significantly alleviated local inflammation and facilitated the formation of mature cartilage tissue. In a rabbit tracheal window defect model, the scaffold markedly reduced granulation tissue formation and preserved luminal patency, ultimately yielding excellent repair outcomes. In conclusion, XN bulk‐modified PEUU represents a dual‐function strategy that combines tailorable mechanical compliance with sustained anti‐inflammatory activity. This approach significantly promotes tracheal regeneration and repair, offering promising prospects for clinical application.